Losses of Electrical Motor for Borehole Investigating Mechatronical Devices - Gečys, S.; Kripas, M.; Katkevičius, V. (Elektronika ir Elektrotechnika, 2005)
The performances of the electrical motor for borehole investigating devices as well as and the torque-slip one may be eveluated taking into account the supply circuit ( the parameters of the long (till 10000 m) single-core geophysical cable, the ballast complex impedances), reliable motor operating in whole slip range, the limited power supply source, the starting quality,character of load torque to dielectric liquid depending on wide operating medium temperature change interval from –20 oC up to +200 oC. The single-phase asynchronous capasitor motor with solid ferromagnetic rotor is the most suitable for above mentioned conditions. The calculation algorithm of the losses components of the investigating motor supplying through the complex circuit taking into account the peculiarities of operating medium and wide temperature change interval. The power diagram as well as the calculation algorithm and programme of general losses and efficiency of the investigating motor have been created. Ill. 3, bibl. 11 (in Lithuanian; summaries in Lithuanian, English, Russian).